Escaping the trap of Apartaans*: Book review Louw-Potgieter, J (1988) Afrikaner Dissidents: A social psychological study of identity and dissent. Clevedon, & Philadelphia: Multilingual Matters - 1 85359 011 8. - Mare, Gerhard (PINS-Psychology in Society, 2025)
"How, or by means of which proccess(es), does a person, as a member of a specific group, in a specific social, economic and historical context, start to question the political status quo" - that is the task that Louw-Potgieter set herself in her PhD thesis (the basis of the book under review). The study presented in book form is of "white, politically left wing Afrikaans speakers", excluding both "coloured" and ultra-right wing Afrikaans speakers (Louw-Potgieter, 1988, p2).